Mitochondrial cytochrome c release may occur by volume-dependent mechanisms not involving permeability transition. - Gogvadze, Vladimir (2004)
The mechanisms regulating mitochondrial outer-membrane permeabilization and the release of cytochrome c during apoptosis remain controversial. In the present study, we show in an in vitro model system that the release of cytochrome c may occur via moderate modulation of mitochondrial volume, irrespective of the mechanism leading to the mitochondrial swelling. In contrast with mitochondrial permeability transition-dependent release of cytochrome c, in the present study mitochondria remain intact and functionally active.